Implementasi Metode Mind Mapping dengan Menggunakan Media Power Point dalam Pembelajaran Nahwu - Anwar Sidik; Muassomah Muassomah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2021)
This reseacrh aims to describe the process and how to implement mind mapping methods using power point media in nahwu learning in third semester students of Arabic education at the Bani Fatah Islamic Institute in Jombang. This type of research is descriptive qualitative using observation and documentation research instruments. The subject and object of research are the third semester students of Arabic education. The results of the reseacrh are as follows: First, the learning process of nahwu by implementing the mind mapping method using power point media is very active with indicators in the form of: a) Students prepare and present learning material with mind mapping created with power point media. b) Discuss between groups after presentation. c) Design learning material with mind mapping using power point media. d) Present the results in sequence. e) Lecturers reflect on learning by involving students. Second, how to implement it as follows: a) The lecturer prepares the material and the projector. b) The lecturer conveys the learning objectives. c) Students and teachers do questions and answers. d) Students are divided into five groups. e) Students present their mind mapping results using power points systematically. f) The lecturer guides the discussion. g) Lecturers appreciate and correct the results of student mind mapping. h) The lecturer explains and summarizes the materials that have been presented by students.